Answer:
([tex]x-1[/tex]) and ([tex]x+\frac{4}{3})[/tex] are the factors of the given equation
It can be written as [tex]6x^2+2x-8=(x-1)(x+\frac{4}{3})[/tex]
Step-by-step explanation:
Given quadratic equation is [tex]6x^2+2x-8=0[/tex]
To find the factored form of the given equation :
[tex]6x^2+2x-8=0[/tex]
By using the formula for quadratic equation [tex]ax^2+bx+c=0[/tex] then the solution is [tex]x=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex] where a and b are coefficients of [tex]x^2[/tex] and x respectively
[tex]x=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
Substitute a=6, b=2 and c=-8 in the above equation we get
[tex]x=\frac{-2\pm \sqrt{2^2-4(6)(-8)}}{2(6)}[/tex]
[tex]=\frac{-2\pm \sqrt{4+192}}{12}[/tex]
[tex]=\frac{-2\pm \sqrt{196}}{12}[/tex]
[tex]=\frac{-2\pm 14}{12}[/tex]
[tex]x=\frac{-2\pm 14}{12}[/tex]
Therefore [tex]x=\frac{-2+14}{12}[/tex] and [tex]x=\frac{-2-14}{12}[/tex]
[tex]x=\frac{12}{12}[/tex] and [tex]x=\frac{-16}{12}[/tex]
[tex]x=1[/tex] and [tex]x=\frac{-4}{3}[/tex]
Therefore ([tex]x-1[/tex]) and [tex](x+\frac{4}{3})[/tex] are the factors of the given equation
It can be written as [tex]6x^2+2x-8=(x-1)(x+\frac{4}{3})[/tex]